2008
DOI: 10.1158/1541-7786.mcr-07-0373
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 as a Molecular Target in a Multimodality-Resistant Phenotype in Tumor Cells

Abstract: We have previously shown that hydrogen peroxideresistant permanent cells are resistant to the cytotoxicity of several exogenous oxidative and anticancer agents including H 2 O 2 , etoposide, and cisplatin; and we refer to this process as an oxidative multimodality-resistant phenotype (MMRP). Furthermore, OC-14 cells contain increased activator protein 1 activity, and inhibition of activator protein 1 reversed the MMRP. In this study, we show that permanent Rat-1 cell lines genetically altered to overexpress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…The CAGE promoter contains binding sites for transcription factors such as ELK-1 and GATA-1, and ChIP assay showed binding of ELK-1 in SNU387 R cells and GATA-1 in Malme3M R cells, respectively (data not shown). Overexpression of DNMT1 was related with a multimodality-resistant phenotype in tumor cells (26), and moreover, overexpression of DNMT1 was seen in c-Fos-overexpressing tumor cells (26). In our study, we actually found a decreased expression of DNMT1 in SNU387 R and Malme3M R cells (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…The CAGE promoter contains binding sites for transcription factors such as ELK-1 and GATA-1, and ChIP assay showed binding of ELK-1 in SNU387 R cells and GATA-1 in Malme3M R cells, respectively (data not shown). Overexpression of DNMT1 was related with a multimodality-resistant phenotype in tumor cells (26), and moreover, overexpression of DNMT1 was seen in c-Fos-overexpressing tumor cells (26). In our study, we actually found a decreased expression of DNMT1 in SNU387 R and Malme3M R cells (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, new therapeutic options are urgently needed. Epigenetic silencing of gene expression, especially that mediated by promoter hypermethylation, plays an important role in the development and progression of PCa, as well as in the emergence of resistance to chemotherapy [17,18]. Thus, DNMTs might constitute a valuable therapeutic target for PCa treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We similarly observed that oxidized LDL downregulates KLF2 expression in endothelial cells ( Figure VII in the online-only Data Supplement), but did not probe the molecular mechanisms responsible for this downregulation. It is noteworthy that DNMTs are impacted by the oxidative milieu, 38 and that oxidized LDL could, thus, affect gene expression via oxidative stress. However, oxidative stress is unlikely to be responsible for the effect of native LDL because p66shc, a master regulator of the cellular redox environment, does not mediate LDL-induced repression of KLF2 ( Figure II in the online-only Data Supplement).…”
Section: Silencing Of Endothelial Klf2 By Ldl 1941mentioning
confidence: 99%